Instagrammable Spaces: Exploring Photogenic Spaces in Pamulang Town Square, South Tangerang City - Imam Subhi Imam Subhi; Hanifa Fijriah Wasnadi Hanifa Fijriah Wasnadi (Program Studi Arsitektur, Fakultas Teknik, Universitas Riau, 2026)
Alun-Alun Pamulang is the first public square in South Tangerang City and was officially inaugurated on 10 March 2023. Since its opening, several facilities within the area have been consistently used by visitors as locations for photography and selfies. This study aims to identify the factors influencing the high utilization of these facilities as photo-taking spaces. The research employed a qualitative method with a case study approach. Based on the results of the content analysis, photographic activities were concentrated in several locations with distinct visual characteristics. However, most photographs used the landmark located in the western part of the site as the primary background, resulting in the majority of photographs being oriented toward the west. The factors influencing the popularity of these photo locations include the use of contrasting colors combined with textures, the application of foreground-background principles, scale and proportion, axes formed through differences in texture, patterns and material types, as well as the presence of blank spaces.